Social Security Coverage and the Labor Market in Developing Countries - Paula Auerbach; María Eugenia Genoni; Carmen Pagés-Serra (Inter-American Development Bank, Research Department, 2005)
This paper analyzes the reasons behind the low rates of contribution to social security programs in developing countries. Using a large set of harmonized household surveys from Latin America we compare contribution patterns among wage employees, for whom participation is compulsory, with contribution patterns among self-employed workers, for whom participation is often voluntary. In all countries, contribution rates among salaried workers are similarly correlated with education, earnings, size of the employer, household characteristics and age. In addition, contribution patterns among salaried workers are highly correlated with contribution patterns among the self-employed. Our results indicate that on average more than 30 percent of the explained within-country variance in contributions patterns may be accounted for by individuals low willingness to participate in old-age pension programs. Nonetheless, we also find evidence suggesting that some workers are rationed out of social security against their will.
Keywords: 330; Gesetzliche Rentenversicherung; Selbstständige; Informeller Sektor; Lateinamerika; Versicherungsschutz